2021
DOI: 10.1200/po.21.00231
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Population Awareness of Cancer Genetic Tests: Implications for Enhancing Equity in Engaging in Cancer Prevention and Precision Medicine

Abstract: PURPOSE Racial and ethnic disparities in genetic awareness (GA) can diminish the impact of personalized cancer treatment and risk assessment. We assessed factors predictive of GA in a diverse population–based sample to inform awareness strategies and reduce disparities in genetic testing. METHODS A cross-sectional study was conducted from July 2019 to August 2019, with the survey e-mailed to 7,575 adult residents in southeastern Pennsylvania and New Jersey. Constructs from National Cancer Institute Health Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Given that the majority of the female respondents had breast cancer (62.5%), the latter two findings may be related to greater public awareness of the availability and benefits of genetic testing for breast cancer, however, as we did not ask about this specifically, there may be other underlying reasons for this result. 38 We also found that having a more distant cancer diagnosis was associated with increased insurance concerns and greater emotional concerns. This may be explained by the fact that participants who are receiving or have recently completed treatment are less concerned with factors such as future insurance coverage and emotional concerns as they are more preoccupied with more immediate heath concerns such as access to care and treatment costs.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Given that the majority of the female respondents had breast cancer (62.5%), the latter two findings may be related to greater public awareness of the availability and benefits of genetic testing for breast cancer, however, as we did not ask about this specifically, there may be other underlying reasons for this result. 38 We also found that having a more distant cancer diagnosis was associated with increased insurance concerns and greater emotional concerns. This may be explained by the fact that participants who are receiving or have recently completed treatment are less concerned with factors such as future insurance coverage and emotional concerns as they are more preoccupied with more immediate heath concerns such as access to care and treatment costs.…”
Section: Discussionmentioning
confidence: 52%
“…For example, being female was also associated with increased insurance concerns, a stronger interest in health benefits, and increased positive outlook on the FACToR scale. Given that the majority of the female respondents had breast cancer (62.5%), the latter two findings may be related to greater public awareness of the availability and benefits of genetic testing for breast cancer, however, as we did not ask about this specifically, there may be other underlying reasons for this result 38 . We also found that having a more distant cancer diagnosis was associated with increased insurance concerns and greater emotional concerns.…”
Section: Discussionmentioning
confidence: 72%
“…31 Creating educational aids that incorporate literacy, numeracy, and cultural barriers is important to consider when adapting counseling models. 32,33…”
Section: Discussionmentioning
confidence: 99%
“…The majority of individuals in these cohorts indicated a self-reported White ancestry, which may have biased the results. The socioeconomic factors demonstrated to impact the utilization of genetic testing were not controlled for in this study ( Gómez-Trillos et al, 2020 ; McKinney et al, 2020 ; Giri et al, 2021 ). While not a focus in this study, Invitae has sponsored testing programs that eliminate potential financial barriers to diagnostic genetic testing for a number of clinical indications, in addition to research initiatives to help facilitate population screening and cascade testing across more diverse groups ( staff reporter, 2021 ).…”
Section: Discussionmentioning
confidence: 99%